The Effect of Image Media on Mathematic Representation Ability of Data Presentation Materials on Learning Online Students of Class IV SD N 064998 Medan - Taruli Marito Silalahi; Fitry Wahyuni (BIRCU, 2022)
The purpose of this research is to determine the effect of image media on mathematical representation ability at data presentation material in online learning of fourth grade students at State Elementary School 064998 Medan Marelan in Academic Year of 2020/2021. This research is an experimental research with quantitative method uses a Quasi experimental research with non equivalent groups pretest – posttest design. This study consisted of two variables, independent variable is image media in online learning and independent variable is the mathematical representation ability of fourth grade students at State Elementary School 064998 Medan Marelan in Academic Year of 2020/2021. The population is all students grade IV State Elementary School 064998 Medan Marelan, Totaling 58 students with sample used were 30 students of class IVA and 28 students of class IVB. The data collection instruments were observation, test and documentation. This research instrument uses test validity, test reliability, level of difficulty and differentiating power of Question. The data analysis used N – Gain calculation, Normality test, Homogenity test and hypotetis testing. The result of this study show that the experimental class has increased, where 4 students with hight interpretation and 26 students with moderate interpretation. The output table of the t – test of experimental class with value Sig. (2 – Tailed) pretest posttest value is 0.000. based on the decision criteria 0.000 < 0.05, Ho is rejected and Ha is accepted. It can be concluded that image media affect the student’s mathematical representation ability at data presentation material in online learning of fourth grade students at State Elementary School 064998 Medan Marelan in Academic Year of 2020/2021.